Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1590/0037-8682-0100-2020
|View full text |Cite
|
Sign up to set email alerts
|

Exercise tests in Chagas cardiomyopathy: an overview of functional evaluation, prognostic significance, and current challenges

Abstract: Patients with Chagas cardiomyopathy (ChC) usually progress with fatigue and dyspnea. Exercise tests are valuable for the functional evaluation of these patients. However, information about the applicability of the exercise tests is scattered, and no studies have systematically reviewed the results. Thus, the present review explored the general aspects and prognostic value of exercise tests in patients with ChC. A literature search of the MEDLINE, Web of Science, CINAHL, Scopus, and LILACS databases was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 58 publications
0
11
0
2
Order By: Relevance
“…in patients with ChC 40 . Two studies included in this review verified the association between VO2peak and HRQoL, assessed using the MLwHFQ and SF-36.…”
Section: Sf-36mentioning
confidence: 93%
See 1 more Smart Citation
“…in patients with ChC 40 . Two studies included in this review verified the association between VO2peak and HRQoL, assessed using the MLwHFQ and SF-36.…”
Section: Sf-36mentioning
confidence: 93%
“…Functional capacity, assessed by both peak oxygen uptake (VO2peak) and field tests, has clinical and prognostic importance in patients with ChC 40 . Two studies included in this review verified the association between VO2peak and HRQoL, assessed using the MLwHFQ and SF-36.…”
Section: Association Between Hrqol and Functional Variables Echocardi...mentioning
confidence: 99%
“…Cardiac remodeling induced by pathogens in ChC can lead to a progressive reduction in cardiac performance with an impact on the functional capacity of individuals. In this context, cardiac damage, abnormalities of the sympathetic-vagal balance, poor diet, chronic and systematic inflammatory process, medications, and physical inactivity could explain intolerance to physical exercise, muscle weakness, and worsening of the quality of life of patients with ChC [1][2][3] .…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen consumption at peak effort (VO 2 peak), metabolic thresholds, ventilatory efficiency (VE/VCO2slope) with gravity marker, and presence of periodic breathing (PB) have been evaluated in the ChC 1,2,4 . However, few studies have investigated the effects of a combined formal exercise program with aerobic exercise and strength exercise in patients with ChC with LVD.…”
Section: Introductionmentioning
confidence: 99%
“…In the setting of ChC, Ritt et al 6 reported that the VE/VCO 2 slope was the only independent predictor of a worse prognosis (cut-off value of 32.5) among the variables evaluated by the CPET. However, unlike heart failure, few studies have evaluated the VE/VCO 2 slope in patients with ChC 7 , and no study has demonstrated the determinants of the VE/VCO 2 slope in this population. Thus, the present study aimed to verify the clinical, echocardiographic, and functional determinants of the VE/VCO 2 slope in patients with ChC.…”
mentioning
confidence: 99%